Analysis Of Hemoglobin Levels And Erythrocyte Sedimentation Rate In Diabetes Mellitus Patients In Santa Elisabeth Hospital Laboratory Medan In 2022 - Seri Rayani Bangun; Barce Inel Crevis Gulo; David Sumanto Napitupulu (Sean Institute, 2022)
Hemoglobin Levels and erythrocyte sedimentation rate in people with diabetes mellitus often experience a decrease and increase due to uncontrolled eating patterns, drinking medicine is not routine, exercise is not regular. This can cause the patient to experience anemia due to decreased hemoglobin and inflammation due to increased erythrocyte sedimentation rate. Santa Elisabeth Hospital Medan in 2022 This study used a descriptive analytic design. The population in this study 46 people sample 31 with the technique of purposive sampling. Data collection is done using a check tool hemoglobin levels, namely hematology analyzer pentra ABX 60 and for erythrocyte sedimentation rate using the Westergreen method. The results showed that the minimum value of hemoglobin level was 1 and the maximum value of hemoglobin was 4, the average value of hemoglobin was 2.58 with a standard deviation of 0.848. Results The minimum value for the erythrocyte sedimentation rate is 2 and the maximum value of the erythrocyte sedimentation rate is 4, the average value of the erythrocyte sedimentation rate is 2.74 with a standard deviation of 0.930. So, the results of the study there was a decrease in hemoglobin levels and an increase in the level of erythrocyte sedimentation rate. Suggestions in conducting research on hemoglobin examination and erythrocyte sedimentation rate follow the procedure according to the SOP and use complete personal protective equipment.